ЭЛИТАРНЫЕ ОРИЕНТАЦИИ ПРОФЕССИОНАЛЬНОГО САМООПРЕДЕЛЕНИЯ В ОБРАЗОВАТЕЛЬНОЙ СРЕДЕ - Ермакова Светлана Станиславовна; Иванова Оксана Станиславовна (World Science, 2019)
The paper deals with topical issues of vocational guidance for young people, specifies innovative forms of vocational orientation in the educational environment. The active character of the subject of professional self-determination is emphasized, the psychological and pedagogical conditions of the formation of such activity are highlighted. Special attention is paid to the active position of the higher education institution and its teachers. The effectiveness of vocational guidance work is summarized in the context of the introduction of scientifically based approaches to professional agitation. Presents examples of campaign activities in the educational environment used in the study.